The Assassinaton of Mahatma Gandhi in 1948 - Guruh Prasetyo; Marjono Marjono; Sumarjono Sumarjono (History Education, University of Jember, 2018)
The sovereignty given to India and Pakistan in separate way at 1947, became the beginning of disturbance which is occured in India. Therefore, the conveyance of sovereignty separately caused a prolonged conflict in India and Pakistan. As a nationalist of India, Mahatma Gandhi wanted a unity of society in India as well as in Pakistan. Moreover, the difference thoughts were frequently occured among Mahatma Gandhi and several figures of fanatic people on the mission of peace series in India and Pakistan. This situation caused a conspiration by the group of fanatic people through assassination on Mahatma Gandhi. The conspiracy had done by a person in a particular capacity who comes from Mahasabha Party and Rhatrya Swayam Sevak Sangha Organizatiom. In addtition, issue of districts distribution was also the reason of continuous conflict occured in India and Pakistan. According to this situation, this research is proposed to explain the series of conspiracy which have done by the conspirator through phenomenon of throwing grenade to Gandhi's assassination in 1948 at Birla House. As the results, at that moment, disturbance were more considerable in India. Thus, disturbance occured in the area of Jammu and Khasmir were the main impact of disturbance which is never dispersed. Keywords: Conspiration, Ghandi, India, Pakistan